Lemierre Syndrome: A Diagnosis behind the Veil - Pak-Ho Au; Kelechi Nwabara; Nanuli Gvazava; Shannon Ejiofor; Ghulam Ghous (Case Reports in Infectious Diseases)
Lemierre syndrome (LS) is a rare, serious infection that is often misdiagnosed, as it frequently mimics common upper respiratory infections. It is even rarer for LS to be preceded by a viral infection. We share a case of LS in a young man who presented to the Emergency Department with COVID-19 viral infection followed by a subsequent LS diagnosis. The patient’s condition initially worsened despite treatments for COVID-19 and was subsequently started on broad-spectrum antibiotics. He was then diagnosed with LS after blood cultures grew Fusobacterium necrophorum, and antibiotics were adjusted accordingly, resulting in improvement of symptoms. Even though LS is often recognized as a sequela of bacterial pharyngitis, preceding viral infections, including COVID-19, might be a risk factor that contributes to the development of LS.